Development of heavy metal passivators in residue fluid catalytic cracking process - Salahshour, Peyman; Yavari, Mansoureh; Güleç, Fatih; Karaca, Huseyin; Tarighi, Sara; Habibzadeh, Sajjad (Journal of Composites and Compounds, 2022)
The advancement of residual fluid catalytic cracking (RFCC) is significantly influenced by the development of heavy metals passivation technology. Resids often include larger concentrations of heavy metals (Ni, V, and Fe) than gas oils, primarily in the form of porphyrin complexes and salts of organic acids. Under cracking conditions, metals, especially Ni and V in residues and gas oil deposit on the cracking catalyst and induce adverse dehydrogenation reactions. The catalyst's zeolite component is destroyed by these metals. While reducing the yield of gasoline, active metals increase the yields of coke and hydrogen. Because most cracking FCC units can only tolerate limited amounts of coke and hydrogen, the level of heavy metals on the catalyst needs to be kept under control in order to achieve maximum productivity and profit. Metal passivation enhances catalytic activity and/or selectivity to more desired products by minimizing the detrimental effects of contaminating metals. In this study, we will review heavy metals deactivation mechanism in RFCC process and the potential technological solutions to the catalyst deactivation concern.